Rapid northern hemisphere ice sheet melting during the penultimate deglaciation - Heather M. Stoll; Isabel Cacho; Edward Gasson; Jakub Sliwinski; Oliver Kost; Ana Moreno; Miguel Iglesias; Judit Torner; Carlos Perez-Mejias; Negar Haghipour; Hai Cheng; R. Lawrence Edwards (Nature Communications, 2022)
Stalagmites from NW Iberia record the rapid demise of large ice sheets during the penultimate deglaciation, and reveal decadal-scale feedbacks between warming and ice melting.